Design issues of a passive shielded WPT prototype with regard to safety limits against EM radiation - Tristan Schoenfelder; Vladimir Kindl; Michal Frivaldsky (Results in Engineering)
This paper presents the development and optimization of a passively shielded WPT (Wireless Power Transfer) prototype that ensures compliance with the international limits for magnetic field exposure of the ICNIRP (International Commission on Non-Ionizing Radiation Protection) and the IEEE/ICES (International Committee on Electromagnetic Safety). The aim is to optimize material consumption, weight and costs when building a WPT prototype by following a structured approach and using software-based methods such as finite element analysis (FEA), without compromising safety and energy transmission efficiency. For this purpose, different ferrite shielding arrangements are examined and evaluated on the basis of various parameters. In addition to the shielding, the selection of suitable materials and the design of the overall system is a central topic. By comparing the simulation and measurement results, the functionality of the defined procedure for creating a WPT setup is demonstrated. Furthermore, the results prove the safety of the optimized shielding concept with regard to ICNIRP and IEEE limit value specifications. The work provides important insights into the choice of materials and the design of passive shielding for safe and efficient WPT systems.